The Evaluation of In Vitro Digestibility Methods of Separation and Extrusion of Palm Kernel Cake as Raw Material for Poultry Feed - Lidya Foni; Heri Ahmad Sukria Sukria; Yuli Retnani; Sazli Tutur Risyahadi Risyahadi (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2026)
Palm kernel cake (PKC) is a year-round by-product of the palm oil industry that is affordable and rich in protein nutrients. However, the main obstacle to utilizing PKC is its high shell fraction, which results in high crude fiber content and low nutrient digestibility in poultry. This study aimed to evaluate the in vitro digestibility of PKC processed through separation and extrusion methods as poultry feed ingredients. There were three treatments with four replicates, namely P1 (untreated PKC), P2 (sifted PKC), and P3 (PKC resulting from a combination of sifting and extrusion). The results showed that the treatments had a significant effect (p<0.05) on nutrient digestibility. The sieving treatment resulted in higher crude protein digestibility compared to the other two treatments, while the combination of sieving and extrusion increased crude fiber digestibility but was not significantly different from the sieving treatment. Processing PKC through screening or a combination of screening and extrusion can increase crude protein and crude fiber digestibility in vitro. However, the highest crude protein digestibility was obtained in the screening treatment.